2017
DOI: 10.1038/s41598-017-10644-z
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor Tu is a multifunctional and processed moonlighting protein

Abstract: Many bacterial moonlighting proteins were originally described in medically, agriculturally, and commercially important members of the low G + C Firmicutes. We show Elongation factor Tu (Ef-Tu) moonlights on the surface of the human pathogens Staphylococcus aureus (SaEf-Tu) and Mycoplasma pneumoniae (MpnEf-Tu), and the porcine pathogen Mycoplasma hyopneumoniae (MhpEf-Tu). Ef-Tu is also a target of multiple processing events on the cell surface and these were characterised using an N-terminomics pipeline. Recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 148 publications
1
85
0
Order By: Relevance
“…Trypsin shaving of M. pneumoniae cells was carried out as described previously 12 . Shaving was for 5 minutes at 37 °C and released peptides were trypsin digested a second time before analysis by LC-MS/MS.…”
Section: Liquid Chromatography Tandem Mass Spectrometry (Lc-ms/ms) Anmentioning
confidence: 99%
“…Trypsin shaving of M. pneumoniae cells was carried out as described previously 12 . Shaving was for 5 minutes at 37 °C and released peptides were trypsin digested a second time before analysis by LC-MS/MS.…”
Section: Liquid Chromatography Tandem Mass Spectrometry (Lc-ms/ms) Anmentioning
confidence: 99%
“…They harbour a specific OMP for their export and one among the best-studied is TolC from E. coli [54]. Elongation factor TU is a GTPase also known to perform moonlighting functions on the surface of human pathogens acting as a multifunctional adhesin [55].…”
Section: Degs Pertaining To Virulence Factorsmentioning
confidence: 99%
“…These results suggest that the NF-jB activation may be related to the anti-apoptotic activity of LAMPs. Some reports have shown that mycoplasma can activate NF-jB through TLRs [18,32]. It could be presumed that M. genitalium lipoproteins could inhibit apoptosis by activating NF-jB through TLR2.…”
Section: Comparative Analysismentioning
confidence: 99%